Attenuation of Geopathic Stress by Using NAAVRAJ Attenuation Technique (International Journal of Engineering and Computer Science, 2018)
Geopathic Stress is the energy emitted from earth crust in Nadir direction which affects the normal functioning of human body. The relation between Geopathic Stress and occurrence of accidents has already been proved. Geopathic Stress has an adverse impact on built environment. It is very important to attenuate the Geopathic stress zones to decrease the harmful effects of it. Rate of accidents on Highways and Expressways is more as traffic volume is more. From the study, it is concluded that majority of accidents occur on Geopathic Stress zone only. The work is carried out to attenuate Geopathic Stress zones to reduce the rate of accidents on Expressway as Geopathic Stress is closely associated with change in reaction time of driver which ultimately results in accident. Attenuation of Geopathic Stress zone has been done by using well established NAAVRAJ attenuation technique.